A 1 cm space debris impact onto the Sentinel-1A solar array. (August 2017) - Krag, H.; Serrano, M.; Braun, V.; Kuchynka, P.; Catania, M.; Siminski, J.; Schimmerohn, M.; Marc, X.; Kuijper, D.; Shurmer, I.; O'Connell, A.; Otten, M.; et al.
Abstract: Sentinel-1A is a 2-ton spacecraft of the Copernicus Earth observation program operated by ESA's Space Operations Centre in Darmstadt, Germany. Sentinel-1A and its sister spacecraft Sentinel-1B operate in a sun-synchronous orbit at about 700 km altitude. On 2016/08/23 17:07:37 UTC, Sentinel-1A suffered from an anomaly resulting in a sudden permanent partial power loss and significant impulsive orbit and attitude changes. A deeper investigation identified that an impulsive orbit change against flight direction of 0.7 mm/s, estimated at the time of the event, gave the best results in terms of GPS residuals. At the same time, a peak attitude off-pointing of 0.7° (around the spacecraft yaw axis) and peak attitude rate increase of 0.04°/s (around the same axis) were observed. The simultaneous occurrence of these anomalies, starting from a sudden attitude change and ending with a permanent partial power loss, made an MMOD (Micro-Meteoroid and Orbital Debris) impact onto a solar array a possible explanation for this event. While the spacecraft is able to continue its mission nominally, a detailed investigation involving ESA's Space Debris and Flight Dynamics experts was conducted. An MMOD impact as an explanation gained further credibility, due to the pictures of the solar array taken by the on-board camera displaying a significant damage area. On September 7th, JSpOC (US Joint Space Operations Centre) informed SDO on 8 tracked fragments that are considered to be released by Sentinel-1A after the impact. This paper addresses the analysis that was performed on the data characterising the attitude and orbit change, the on-board camera image, and the tracked fragments. The data helped to identify the linear momentum vector while a flux analysis helped to identify the origin of the impactor and allowed to understand its mass and size characteristics. Highlights: Orbital debris has been identified as a root cause of a Sentinel-1A anomaly. The damage location was determined by an on-board camera. This allowed to reconstruct the impulse vector of the impactor. Several trackable fragments have been released. On-board cameras are recommended for failure analysis.